EL SIMULASI SISTEM PELAYANAN RESTORAN YURAKU KOMPLEK DâBEST KELAPA GADING - Sukwadi, Ronald (Industrial and Systems Engineering Assessment Journal (INASEA), 2007)
Yuraku Restaurant in Kelapa Gading area which opens only from 6 p.m to 10Â p.m., is very famous for its good taste. Yuraku is also well known for its service system inÂ which the server it self will serve the food for the customer, so that they donât have toÂ serve their own food.The research aims to develop a simulation model from the realÂ system currently employed at Yuraku Restaurant. The research consisted of four mainÂ steps namely description model, conceptual development model, input data analysis, andÂ simulation modeling. During input data analysis, homogenity test using Kruskal WallisÂ test and distribution fitting were conducted. Output of ARENA simulation allowed aÂ deeper understanding of the real condition of Yurakuâs system. It is shown that the systemÂ performance of Yuraku restaurant is good enough, though some improvements areÂ needed in the long term.